Pemasaran Kreatif untuk Peningkatan Usaha Pelaku IKM dalam Mendorong Pertumbuhan Ekonomi Lokal - Yasmir, Yasmir; Susanto, Joko; Anggraini, Zepa; Dolly, Fajar Ifan (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2025)
Small and Medium Industries play an irreplaceable role in spurring local economic growth in Indonesia. The contribution of Small and Medium Industries to Gross Domestic Product and job creation is very significant. However, Small and Medium Industries face major challenges, including limited marketing knowledge and skills, limited access to promotional media and digital platforms, and intense competition with imported products. To overcome this challenge, a service program was implemented in Sinar Gading Village, Merangin Regency, aimed at improving the creative marketing capabilities of Small and Medium Industry players. This program involves 40 participants from various Small and Medium Industry sectors, through intensive training that includes creative marketing techniques, branding, digital marketing, product innovation and e-commerce. The results of this program show a significant increase in participants' marketing knowledge and skills, which has a positive impact on sales turnover, market expansion, and the formation of new collaboration networks between Small and Medium Industry players. Even though there are still obstacles such as limited access to technology and traditional mindsets, this initiative has succeeded in increasing the competitiveness of local Small and Medium Industries and encouraging economic growth in the area. Ongoing support is essential to strengthen the results achieved and ensure long-term success.